PENDAMPINGAN PENATAUSAHAAN TANAH ULAYAT NAGARI UNTUK PEMBERDAYAAN MASYARAKAT DI NAGARI SUNGAYANG KABUPATEN TANAH DATAR: PENDAMPINGAN PENATAUSAHAAN TANAH ULAYAT NAGARI UNTUK PEMBERDAYAAN MASYARAKAT DI NAGARI SUNGAYANG KABUPATEN TANAH DATAR - Warman, Kurnia; Ferdi, Ferdi (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2024)
If we define the provisions of Article 5 and General Elucidation number III (1) of Law Number 5 of 1960 on the Basic Agrarian Principles (UUPA), it can be concluded that the applicable Agrarian law is customary law, as long as it does not conflict with national and state interests. In the context of West Sumatra, according to Minangkabau Customary Law, all land and forests from a single tree, a single stone to a single blade of grass, from the height to the sky and the depth to the bowels of the earth are ulayat. This means that ulayat rights can be in the form of natural resources including land to the underground and space above the territory of indigenous peoples. Article 19 paragraph (1) of Law Number 5 of 1960 concerning Basic Agrarian Principles has actually instructed from the beginning that to ensure legal certainty by the Government, land registration is carried out throughout the territory of the Republic of Indonesia according to the provisions regulated by Government Regulations, including here, namely tanah ulayat. Government Regulation No. 18 of 2021 concerning Management Rights, Land Rights, Flat Housing Units, and Land Registration opens up opportunities for tanah ulayat to be registered and granted management rights over it. To uphold this regulation, in 2021 the Ministry of ATR/BPN in collaboration with the Faculty of Law, Universitas Andalas organized an inventory and identification of tanah ulayat nagari in West Sumatra Province and was then followed up with Pilot Project activities that are currently underway, one of those activities is in Nagari Sungayang, Tanah Datar Regency. This activity aims to provide legal certainty to the tanah ulayat of the indigenous people of Nagari Sungayang, Tanah Datar Regency so that the rights of indigenous people are protected.